Psychosocial aspects of exercise and physical activity in childhood - Kipp, L. E. (Pediatric Exercise Science, 2015)
Thematischer Kommentar zu 2 Themen: A. Positive Youth Development Through Physical Activity—Evaluating Effectiveness Weiss MR, Bolter ND, Kipp LE. Assessing impact of physical activity-based youth development programs: Validation of the Life Skills Transfer Survey (LSTS). Res Q Exerc Sport. 2014; 85:263-278. B. Optimal Functioning in Youth Sport—The Contribution of Self-Determination Theory to Understanding Mental Toughness